The Factors Influencing Children’s Helping Behavior: The Roles of Cognition and Empathy Concern - Mingyue Liang; Hongfang Mo; Jipeng Duan (Behavioral Sciences)
Helping behavior plays an important role in children’s social interaction and personality development. This study used a situational test method to investigate the effects of cognition and empathy concern on helping behavior in children aged 6–12. The results revealed that empathy concern had a significant effect on children’s helping behavior compared to cognition. By inducing varying levels of empathy concern through prosocial songs, the subjects exhibited significant differences in helping behavior, with children in the high empathy concern group demonstrating significantly higher levels of helping behavior. Therefore, as for the education on children’s helping behavior, teachers should pay special attention to the factor of empathy concern, and the educational strategy of activating empathy concern can improve the effectiveness of children’s helping behavior education.